Unexpected cleavage of upper rim-bridged calix[4]arenes leading to linear oligophenolic derivatives - Slavík, P; Dvořáková, H; Krupička, M; Lhoták, P (Organic & biomolecular chemistry, 2018)
Regioselective meta-mercuration followed by Pd-catalysed intramolecular bridging gave birth to a novel type of calixarene bearing a single bond bridge between the meta positions of the neighboring aromatic subunits. These bridged derivatives possess extremely distorted cavities that imply possible amended properties over common calix[4]arenes. This new type of calixarene reactivity can be documented by acid-/electrophile-mediated cleavage of the basic macrocyclic skeleton leading to open oligomeric structures-the behavior of which has never been observed before in classic calix[4]arenes bearing alkoxy groups on the lower rim.